30- day outcomes in hip fracture patients during the COVID-19 pandemic compared to the preceding year. (2020) - Macey, A. R. M.; Butler, J.; Martin, S. C.; Tan, T. Y.; Leach, W. J.; Jamal, B.
No abstract available